2018
DOI: 10.1007/s40615-018-0518-6
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Racial Disparities in Diabetes Among Primary Care Residents and Preparedness to Discuss Disparities with Patients

Abstract: Many healthcare providers lack the awareness of health disparities among their patients that precedes action to improve outcomes. Limited health disparities training is a probable contributor. We assessed primary care residents' awareness of racial and ethnic disparities in diabetes, their perceived preparedness to discuss health disparities with patients, and their preferences for training and resources to improve their preparedness. Primary care residents (n = 98) affiliated with two teaching hospitals in No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Medically underserved communities (MUC) are defined as specific populations that have a shortage of primary healthcare services or otherwise face unmet healthcare needs [ 4 ]. Healthcare providers often feel ill-equipped to care for these populations, relying on on-the-job training and experience [ 5 ]. One way to address these disparities is through instruction in undergraduate medical education regarding social determinants of health (SDoH) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medically underserved communities (MUC) are defined as specific populations that have a shortage of primary healthcare services or otherwise face unmet healthcare needs [ 4 ]. Healthcare providers often feel ill-equipped to care for these populations, relying on on-the-job training and experience [ 5 ]. One way to address these disparities is through instruction in undergraduate medical education regarding social determinants of health (SDoH) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are needed to consider these aspects when assessing awareness of medication. Seventh, our model's overall association was low, indicating the possibility of other unmeasured factors influencing the low awareness of DM medication, such as another comorbid disease such as kidney disease ( 63 ), healthy lifestyle ( 64 ), education about DM ( 65 ), the number of medicines in the therapy ( 66 ), duration of DM ( 67 ), ethnic background ( 68 ) or medication beliefs ( 69 ).…”
Section: Discussionmentioning
confidence: 91%
“…Another main solution that various studies have pointed for decreasing T2D socioeconomic inequality is financial supports. [ 25 52 57 59 73 76 77 79 85 87 88 97 98 99 100 101 ]…”
Section: Resultsmentioning
confidence: 99%
“…Outreach of telemedicine: Studies have shown that the use of telemedicine, particularly through the outreach of media devices such as cellphones, can increase access to healthcare and help to level the playing field treatment-wise, particularly by increasing penetration of digital devices in all socioeconomic and sociocultural levels. [ 43 100 ]…”
Section: Resultsmentioning
confidence: 99%